In the search of intra and inter-specific balance - Cristina Acasuso-Rivero (Revue de Primatologie)
Before the establishment of political societies there was no constant property and social groups were not governed by an authority. Human aggregation leads into the need for authority and culture conceptualization. Inter and intra-specific interactions have evolved in parallel to the redefinition of these concepts which have always been density dependent. Present human western (or westernized) society lives in big intra-specific aggregations where constant property covers even other species, and where anthropocentrism is in general well accepted and not challenged. As communities keep growing, social pressures and other factors have made human primates away from empathy, which declines proportionally to density increase. The lack of empathy immediately drives to the search of differentiation and uniqueness which is easier to proclaim towards other species, especially to non-human primates as they could represent a threat for its resemblance to our species. All non-human animals have been cast aside, their differences highlighted and the concept of culture redefined in order to take away non-human species the possibility to have a culture. However, there are still human communities which preserve empathy towards other species, accepting non-human cultures; and who are in their search of intra and inter-specific balance. Challenging cultural anthropocentrism and non-human animal property by understanding the inter-specific balance can be achieved by a better understanding of such human communities.